Recycling textile and plastic waste - Horrocks, A. Richard; Burdett, Brian (Woodhead publishing in textiles., 1996)
Edited papers from the 1995 conference Ecotextile - Wealth for Waste in Textiles, organised by Bolton Institute and the British Textile Technology Group.